A study of urban pollution at Kampung Morten Melaka - Dominic Sibih, Fredinand; Mohd Yusof, Noor Fahimah (2008)
The process of the urbanization has contributed to several types of pollution. It happens because of the fast developing process of urbanization. Besides the increasing numbers of natural disasters happened now days contributes to the study of this research. The study examines the major factors of the urban pollution, the effect of the pollution and the level of the awareness towards the implementation of urbanization process. The researchers choose Kampung Morten as examples of the case study based on criteria that fulfill the research requirement and objective. A random sample of 95 respondents that representatative house of Kampung Morten has been selected to answer the research questionnaires. They were asking on several of question in the questionnaire that related to their perception of the urban environment, the effect and their level of the awareness of environment care. The multi stage sampling are been choose to representative data in this study. As the result most of the respondents choose air pollution as the main factors that affected by the urban environment based on vehicles smoke. Meanwhile the level of awareness is good among the respondents but need to be developing from time to time in order to make the place in the good condition and free from any pollution. Based on the overall study regarding the urban environment in Kampung Morten, there’s a lot urbanization development that made by the Malacca local Government Council in way to well develop Kampung Morten as one of main attraction in Tourism Industry in Malacca as the historical state of Malaysia.